A method for extracting titanium and removing impurities from low-quality titanium-containing waste

Through the process of strong magnetic iron removal - staged electrical selection enrichment - oxidative roasting - selective acid leaching and removal, the problem of recycling and utilization of low-quality titanium-containing waste is solved, efficient enrichment and deep impurity removal are achieved, and high-grade titanium-rich materials are obtained, with the advantages of high titanium recovery, low cost and easy industrialization.

CN119242956BActive Publication Date: 2025-03-14CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411773656.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle low-quality titanium-containing waste, and the impurity removal process is complex, resulting in low titanium recovery rate, high energy consumption and cost.

Method used

The process of strong magnetic iron removal - step-by-step electrical selection enrichment - oxidation and roasting - selective acid leaching and removal of impurities is adopted to efficiently enrich and depth decompression of titanium components through the differences in magnetic properties and conductivity, and high-grade titanium-rich materials with grades above 92%.

Benefits of technology

It realizes efficient enrichment and deep removal of low-quality titanium-containing waste, and obtains high-grade titanium-rich materials, with high titanium recovery, simple operation, low cost, and easy to achieve industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242956B_ABST
    Figure CN119242956B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for extracting titanium and removing impurities from low-quality titanium-containing waste, and belongs to the technical field of solid waste resource treatment. The method is to sequentially subject low-quality titanium-containing waste to magnetic separation for iron removal, grinding I, and cascade electrostatic enrichment to obtain a pre-enriched material; the pre-enriched material is placed at a temperature of 800-1000°C for oxidative roasting to obtain a roasted slag containing rutile titanium dioxide; the roasted slag is subjected to grinding II and pickling for impurity removal to obtain a high-grade titanium-rich material product. The method directly obtains a high-grade titanium-rich material product by upgrading and removing impurities from low-quality titanium-containing waste, thereby realizing the high-value utilization of low-quality titanium-containing waste, and the technical route is simple to operate, low in cost, and has high economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the quality of low-quality titanium-containing waste, and in particular to a method for extracting titanium and removing impurities from low-quality titanium-containing waste to prepare high-grade titanium-rich material, belonging to the technical field of solid waste resource treatment. Background Art

[0002] Titanium alloys are widely used in high-end fields such as aerospace, metallurgy and chemical industry, ocean-going ships, biomedicine, etc. due to their excellent properties. In the process of processing titanium sponge into finished titanium alloy materials, about 40% to 60% of the input materials are lost in the form of titanium alloy waste.

[0003] The titanium alloy waste generated during the titanium alloy smelting process is of fixed type and stable composition. However, due to the wide variety of titanium alloy grades, different grades have different chemical composition contents to meet the specific requirements of their service environment, and the titanium grade is mostly between 10% and 50%. At the same time, the quality of corundum abrasives used by different titanium alloy grinding companies varies greatly, resulting in a wide variety of impurity elements in the low-quality titanium-containing waste with high content and poor composition stability, which greatly increases the difficulty of its treatment. In industrial production, titanium alloy grinding waste is regarded as solid waste and piled up on site, and it has not been effectively recycled so far. During the stacking process, waste iron wire and iron filings, surface mineral ash and other fine-grained waste generated by mechanical processing are mixed into the titanium alloy grinding waste, further complicating the physical phase composition and reducing its recycling value.

[0004] A Chinese patent (publication number: CN107399758A) discloses a method for preparing artificial rutile from high-titanium slag, which includes the steps of crushing the high-titanium slag, alkali leaching to remove impurities, modified roasting, acidic impurity removal and calcination. The method is to remove silicon impurities from the high-titanium slag by alkali leaching, modify the slag by sodium calcination to achieve the destruction of the solid solution structure, and then acid leaching to remove impurities such as Fe 2 O 3 、CaO、MgO、Al 2 O 3 The leached slag is finally calcined at high temperature to obtain artificial rutile. This patent is mainly aimed at the titanium alloy waste generated during the smelting process of high-grade titanium alloys. The impurity removal process is complicated and the titanium alloy waste needs to be modified and roasted, which easily leads to low titanium recovery rate, high energy consumption and cost. Summary of the invention

[0005] In view of the defects of the existing technology, the purpose of the present invention is to provide a method for extracting titanium and removing impurities from low-quality titanium-containing waste. The method adopts the process of strong magnetic iron removal-stepped electrostatic enrichment-oxidation roasting-selective acid leaching to achieve efficient enrichment and deep impurity removal of low-grade titanium-containing waste that is difficult to utilize, and directly obtains high-grade titanium-rich material with a grade higher than 92% and a magnesium and calcium content lower than 1.5%. The method has high titanium recovery rate, simple operation, low cost, and is easy to industrialize, and has high social and economic value.

[0006] The low-quality titanium-containing waste involved in the present invention generally refers to titanium-containing waste with a titanium grade of less than 50%, and more preferably refers to titanium-containing waste with a titanium grade of less than 40%.

[0007] The main phase of the high-grade titanium-rich material product involved in the present invention is rutile titanium dioxide, and the grade is higher than 92%, and the magnesium and calcium contents are lower than 1.5%.

[0008] In order to achieve the above technical objectives, the present invention provides a method for extracting titanium and removing impurities from low-quality titanium-containing waste. The method is to sequentially subject the low-quality titanium-containing waste to magnetic separation for iron removal, grinding I and cascade electrostatic enrichment to obtain a pre-enriched material; the pre-enriched material is subjected to oxidative roasting at a temperature of 800-1000°C to obtain a calcined slag containing rutile titanium dioxide; the calcined slag is subjected to grinding II and acid washing for impurity removal to obtain a high-grade titanium-rich material product.

[0009] The key to the technical solution of the present invention is that it adopts a comprehensive treatment process of strong magnetic iron removal-step electrostatic enrichment-oxidation roasting-selective acid leaching impurity removal, which can improve and enrich low-quality titanium-containing waste that is difficult to be directly used, as well as deeply remove impurities, and obtain high-quality rutile titanium dioxide with a grade higher than 92%. More specifically, in view of the phase composition and physical property characteristics of low-quality titanium-containing waste, the present invention utilizes the difference in magnetism and conductivity between the metal impurity component and the useful metal titanium component, first removes iron by strong magnetic force, and then removes most of the magnetic and non-conductor impurities by step electrostatic separation, thereby achieving efficient quality improvement and enrichment of titanium components in low-quality titanium-containing waste. On this basis, the pre-enriched material is oxidized and roasted at an appropriate temperature. During the oxidative roasting process, the low-valent titanium component that is easily soluble in acid can be completely converted into rutile titanium dioxide with a stable configuration. Based on the acid resistance of rutile titanium dioxide, it is beneficial to the subsequent process of impurity removal by pickling, while greatly reducing the loss of titanium and improving the titanium recovery rate. On the other hand, the high-temperature oxidation process can destroy the alloy phase structure in the titanium slag, which is conducive to the penetration of acid solution, and most of the impurity components such as Fe, Ca, Mg, Al are converted into oxide components that are easily soluble in acid solution. Through further acid leaching, the impurity components can be selectively leached, thereby purifying titanium dioxide to obtain high-grade titanium-rich material products.

[0010] As a preferred solution, the low-quality titanium-containing waste includes at least one of scraps and / or cuttings generated during the production, casting, processing or forming of titanium alloys.

[0011] As a preferred solution, the grinding I controls the particle size of the material to be between 40 mesh and 180 mesh. The particle size of low-quality titanium-containing waste will significantly affect the effect of electrostatic separation. Too coarse particle size will lead to an insignificant electrostatic separation effect and poor titanium component enrichment effect. Too fine particle size will lead to an increase in the conductive material in the non-conductive tailings, reducing the electrostatic recovery rate and yield. Therefore, the particle size of the material needs to be controlled within an appropriate range before entering the electrostatic separation.

[0012] As a preferred solution, during the cascade electrostatic separation, the upper electrostatic separation concentrate is used as the raw material for the next electrostatic separation, and the cascade electrostatic separation includes 1 to 3 electrostatic separation processes, and the electrostatic separation condition parameters are: the roller speed is 80 to 140 rpm, the static electrode voltage is 18 to 24 kV, and the roller speed decreases with the increase of the number of electrostatic separations. Generally speaking, the electrostatic separation products include conductor concentrate, intermediate conductor and non-conductor tailings. The titanium-containing components in low-quality titanium-containing waste are mainly titanium alloys and titanium oxides with good conductivity, while the impurity components have weak conductivity. During the electrostatic separation, the titanium-containing components mainly enter the conductor concentrate, while the impurity components mainly enter the non-conductor tailings and the intermediate conductor. Through the cascade electrostatic separation of the conductor concentrate, the titanium-containing components can be deeply enriched and recovered. During the electrostatic separation, if the roller speed is too fast, the centrifugal force is large, and the impurity content in the conductor concentrate will increase; if the speed is too slow, the intermediate conductor with slightly weaker conductivity will be close to the roller surface, and the titanium-iron content in the non-conductor tailings will increase. As the number of electrostatic separation increases, the gradual slowing down of the roller rotation number can achieve deep removal of impurity components in the conductor concentrate. The increase in static electrode voltage can effectively increase the titanium content and recovery rate in the electrostatic conductor concentrate. However, too high an electrostatic separation voltage will lead to a decrease in the yield of the electrostatic conductor concentrate and the recovery rate of the titanium component. This is because some titanium-containing components with weaker conductivity transfer induced charges slowly and fall into the semiconductor bin as the roller rotates, resulting in the loss of titanium-containing components.

[0013] As a preferred solution, the number of electro-selections included in the cascade electro-selection is determined according to the titanium grade in the titanium-containing waste. When the titanium grade is greater than 35%, only one electro-selection is performed, when the titanium grade is 25% to 35%, two electro-selections are performed, and when the titanium grade is less than 25%, three electro-selections are performed. If the titanium grade of the titanium-containing waste is relatively high, the impurity components can be removed by a single electro-selection, and further increasing the number of electro-selections will not improve the titanium grade much. If the titanium grade of the titanium-containing waste is relatively low, the enrichment effect of the titanium component in a single electro-selection is weak, and it is difficult to achieve efficient removal of the impurity components. A better titanium enrichment and recovery effect can be achieved through multiple cascade electro-selections, but too many electro-selections will lead to a lower titanium recovery rate, while increasing energy consumption and affecting production efficiency.

[0014] As a preferred solution, the oxidation roasting is carried out in an oxygen-containing atmosphere. The oxygen-containing atmosphere is, for example, an air atmosphere or a pure oxygen atmosphere. As a preferred solution, the oxidation roasting time is 2 to 4 hours. Part of the titanium in the pre-enriched material exists in the form of metallic titanium and low-valent titanium oxide compounds soluble in acid solution. It can be oxidized to high-valent rutile titanium dioxide that is difficult to dissolve in hydrochloric acid / nitric acid by high-temperature roasting in an air atmosphere or an oxygen atmosphere, while most of the other metal impurity components exist in the form of oxides soluble in hydrochloric acid / nitric acid, and the physical phase structure of the phase existing in the form of alloy solid solution will be destroyed during the oxidation roasting process, which is beneficial to the subsequent acid leaching process and provides the necessary conditions for the separation of titanium-containing components and impurity components during the acid leaching process. The roasting conditions during the oxidation roasting process are relatively important for the oxidation reaction of metallic titanium and low-valent titanium oxides. If the roasting temperature is too low or the time is too short, it is difficult for the titanium-containing component to be completely converted into titanium dioxide. If the roasting temperature is too high or the time is too long, it will not only increase energy consumption, but also may cause the titanium-containing component to react with impurities, thereby affecting the subsequent leaching effect.

[0015] As a preferred solution, the particle size of the material controlled by grinding II is less than 180 mesh. The particle size of the roasted slag will affect the probability of collision and contact between the particles and the solution medium, thereby affecting the leaching effect of the impurity elements. In particular, the titanium-rich slag is easy to stick together into blocks after oxidation roasting, and it is difficult to achieve effective leaching of the impurity components by direct leaching. Reducing the material particles by grinding and screening can improve the leaching rate of the impurity components, but excessive grinding does not significantly improve the impurity leaching rate.

[0016] As a preferred solution, the pickling and impurity removal uses a hydrochloric acid solution and / or a nitric acid solution with a mass concentration of 10% to 30% as a washing liquid. The pickling process uses a hydrochloric acid solution and / or a nitric acid solution. Nitric acid and hydrochloric acid can ensure that impurities such as Fe, Ca, Mg, and Al fully enter the solution without forming low-solubility salts. At the same time, the acid concentration is relatively low, which can avoid the loss of titanium and obtain a high titanium recovery rate.

[0017] As a preferred solution, the conditions for pickling and impurity removal are: liquid-solid ratio of 3-8 mL: 1 g, temperature of 50-90 ° C, and time of 1-3 h. During the leaching process, the acid concentration and liquid-solid ratio have an important influence on the reaction rate and impurity leaching rate. If the acid concentration is too low or the liquid-solid ratio is small, the diffusion rate is slow and the impurity elements cannot be completely leached. When the concentration increases or the liquid-solid ratio increases, the reaction rate and dissolution degree will accelerate. Appropriate acid concentration and liquid-solid ratio are conducive to the removal of impurities in the leaching process, while reducing the amount of acid as much as possible. At the same time, it can be seen from the thermodynamic analysis of the leaching process that increasing the leaching temperature can improve. Increasing the leaching temperature can increase the diffusion coefficient, reaction activity and reaction rate constant of the reactants, which is conducive to improving the kinetic rate of the leaching reaction. However, too high a leaching temperature will lead to rapid volatilization of the acid, which is not conducive to the removal of impurities. Prolonging the reaction time can make the impurities react more fully, thereby improving the impurity removal rate.

[0018] As a preferred solution, the high-grade titanium-rich material product has a titanium dioxide mass content of 92% to 95%, and a magnesium and calcium mass content of less than 1.5%.

[0019] The low-quality titanium-containing waste of the present invention is first subjected to magnetic separation to remove iron, and then subjected to cascade electrostatic separation enrichment. This is mainly because low-quality titanium-containing waste usually contains a certain amount of iron filings, and the iron filings are also conductive. Therefore, the iron filings are removed in advance by utilizing the difference in magnetic properties, otherwise the iron filings will enter the electrostatically separated concentrate and reduce the titanium grade of the product.

[0020] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0021] 1) The present invention adopts strong magnetic iron removal-tiered electrostatic separation to achieve efficient enrichment and recovery of titanium components in low-quality titanium-containing waste. The titanium grade of the electrostatic pre-enriched material obtained is significantly improved, which effectively reduces the acid consumption of subsequent chemical impurity removal.

[0022] 2) The present invention converts metallic titanium and low-valent titanium oxides soluble in hydrochloric acid / nitric acid into rutile titanium dioxide that is insoluble in hydrochloric acid / nitric acid through oxidative roasting. At the same time, part of the alloy phase structure is destroyed, and the metal impurity components exist in the form of oxides soluble in hydrochloric acid / nitric acid, thereby providing the necessary conditions for separating the titanium-containing components and the impurity components during the acid leaching process.

[0023] 3) The present invention uses low-quality titanium-containing waste as raw material and adopts oxidative roasting-selective acid leaching to remove impurities. It not only prepares a high-grade titanium-rich material product with a titanium dioxide mass content of 92% to 95%, but also has a high titanium recovery rate. The technical route is simple to operate, low in cost, easy to industrialize, and has high social and economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1This is the XRD spectrum of the high-grade titanium-rich material product prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The following examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention. Example 1

[0026] The grinding waste produced by a titanium alloy processing plant is used as raw material, with a particle size of less than 20 meshes, a titanium grade of 18.36%, and main impurity components including Ca, Mg, Al, and Si, with contents of 6.04%, 5.03%, 14.63%, and 3.12%, respectively. First, a strong magnetic iron remover is used to remove iron from it to obtain a pre-treated product; the pre-treated product is ground and sieved to a particle size of 40 mesh to 180 meshes, and then a roller-type high-voltage electrostatic separator is used for three-stage electrostatic separation, the diameter of the electrostatic separation roller is 300mm, the roller speeds of the three electrostatic separations are 120rpm, 100rpm, and 80rpm, respectively, the diameter of the static electrode is 33mm, and the static electrode voltage is 21kV. The conductor concentrate from the first electrostatic separation is collected as the raw material for the second electrostatic separation, and the conductor concentrate from the second electrostatic separation is used as the raw material for the third electrostatic separation. The conductor concentrate obtained from the third electrostatic separation is the electrostatic pre-enrichment material. The electrostatic pre-enriched material was oxidatively roasted in an air atmosphere at a temperature of 950°C for 3 hours. After cooling, the roasted product was ball-milled in a planetary ball mill until the material size was less than 180 mesh. The ball-milled material was leached with 30% hydrochloric acid at 70°C for 2 hours, and the leaching liquid-solid ratio was 5mL / g. After filtering, washing and drying, a high-grade titanium-rich material product was obtained. After testing, the titanium dioxide content of the product was 92.43%, the titanium phase was rutile, the calcium magnesium (CaO+MgO) impurity content was 1.25%, and the titanium recovery rate was 73.58%. Example 2

[0027] The grinding waste produced by a titanium alloy processing plant was used as raw material, with a particle size of less than 20 meshes, a titanium grade of 39.87%, and the main impurities including Ca, Mg, Al, and Si, with contents of 4.78%, 4.43%, 9.88%, and 3.92%, respectively. First, a strong magnetic iron remover was used to remove iron from it to obtain a pre-treated product; the pre-treated product was ground and sieved to a particle size of 40 mesh to 180 meshes, and then a roller-type high-voltage electrostatic separator was used for single electrostatic separation. The diameter of the electrostatic separation roller was 300 mm, the roller speed of the electrostatic separation was 140 rpm, the diameter of the static electrode was 33 mm, and the static electrode voltage was 22 kV. The conductor concentrate obtained by electrostatic separation was the electrostatic pre-enrichment material. The electrostatic pre-enrichment material was oxidized and roasted in an air atmosphere at a roasting temperature of 800 ° C and a roasting time of 4 h. After the roasted product was cooled, it was ball-milled in a planetary ball mill until the material particle size was less than 180 meshes. The ball-milled material was leached with 30% nitric acid at 90°C for 1h, with a leaching liquid-solid ratio of 3mL / g. After filtering, washing and drying, a high-grade titanium-rich material product was obtained. After testing, the titanium dioxide content of the product was 94.12%, the titanium phase was rutile, the calcium magnesium (CaO+MgO) impurity content was 1.01%, and the titanium recovery rate was 86.42%. Example 3

[0028] The grinding waste produced by a titanium alloy processing plant is used as raw material, with a particle size of less than 20 meshes, a titanium grade of 18.36%, and main impurity components including Ca, Mg, Al, and Si, with contents of 6.04%, 5.03%, 14.63%, and 3.12%, respectively. First, a strong magnetic iron remover is used to remove iron to obtain a pre-treated product; the pre-treated product is ground and sieved to a particle size of 40 mesh to 180 meshes, and then a roller-type high-voltage electrostatic separator is used for three-stage electrostatic separation, the diameter of the electrostatic separation roller is 300mm, the roller speeds of the three electrostatic separations are 140rpm, 110rpm, and 90rpm, respectively, the diameter of the static electrode is 33mm, and the static electrode voltage is 24kV. The conductor concentrate from the first electrostatic separation is collected as the raw material for the second electrostatic separation, and the conductor concentrate from the second electrostatic separation is used as the raw material for the third electrostatic separation. The conductor concentrate obtained from the third electrostatic separation is the electrostatic pre-enrichment material. The electrostatic pre-enriched material was oxidatively roasted in an air atmosphere at a roasting temperature of 1000°C for 2 hours. After cooling, the roasted product was ball-milled in a planetary ball mill until the material particle size was less than 180 mesh. The ball-milled material was leached with 10% hydrochloric acid at 90°C for 3 hours, and the leaching liquid-solid ratio was 8mL / g. After filtering, washing and drying, a high-grade titanium-rich material product was obtained. After testing, the titanium dioxide content of the product was 92.62%, the calcium magnesium (CaO+MgO) impurity content was 0.87%, and the titanium recovery rate was 71.53%. Example 4

[0029] The grinding waste produced by a titanium alloy processing plant was used as raw material, with a particle size of less than 20 meshes, a titanium grade of 26.87%, and main impurity components including Ca, Mg, Al, and Si, with contents of 5.21%, 3.99%, 12.72%, and 2.13%, respectively. First, a strong magnetic iron remover was used to remove iron from it to obtain a pre-treated product; the pre-treated product was ground and sieved to a particle size of 40 mesh to 180 meshes, and then a roller-type high-voltage electrostatic separator was used for two-stage electrostatic separation. The diameter of the electrostatic separation roller was 300 mm, and the roller speeds of the two electrostatic separations were 130 rpm and 100 rpm, respectively. The diameter of the static electrode was 33 mm, and the static electrode voltage was 19 kV. The conductor concentrate from the first electrostatic separation was collected as the raw material for the second electrostatic separation, and the conductor concentrate obtained from the second electrostatic separation was the electrostatic pre-enrichment material. The electrostatic pre-enrichment material was oxidized and roasted in an air atmosphere at a roasting temperature of 900 ° C and a roasting time of 3 h. After the calcined product is cooled, it is ball-milled in a planetary ball mill until the particle size is less than 180 mesh. The ball-milled material is leached with 20% hydrochloric acid at 50°C for 3 hours, and the leaching liquid-solid ratio is 6mL / g. After filtering, washing and drying, a high-grade titanium-rich material product is obtained. After testing, the titanium dioxide content of the product is 92.33%, the calcium magnesium (CaO+MgO) impurity content is 1.02%, and the titanium recovery rate is 80.24%.

[0030] Comparative Example 1

[0031] Compared with Example 1, the only difference is that a roller-type high-voltage electrostatic separator is used for single electrostatic separation, the diameter of the electrostatic separation roller is 300 mm, the roller speed of the electrostatic separation is 120 rpm, the diameter of the static electrode is 33 mm, and the static electrode voltage is 21 kV. Other operations and conditions refer to Example 1.

[0032] After testing, the titanium dioxide content of the obtained titanium-rich material product was 73.54%, the calcium magnesium (CaO+MgO) impurity content was 10.67%, and the titanium recovery rate was 82.52%.

[0033] It can be seen from this comparative example that for titanium alloy grinding waste with a titanium content of less than 25%, if only a single electrostatic separation is used, the enrichment of the valuable titanium component is not obvious and the titanium grade of the product is low.

[0034] Comparative Example 2

[0035] Compared with Example 1, the only difference is that a roller-type high-voltage electrostatic separator is used for three-stage electrostatic separation, the diameter of the electrostatic separation roller is 300 mm, the roller speeds of the three electrostatic separations are 120 rpm, 100 rpm, and 80 rpm, respectively, the diameter of the static electrode is 33 mm, the static electrode voltage is 28 kV, the conductor concentrate of the first electrostatic separation is collected as the raw material for the second electrostatic separation, the conductor concentrate of the second electrostatic separation is used as the raw material for the third electrostatic separation, and the conductor concentrate obtained in the third electrostatic separation is the electrostatic pre-enrichment material. Other operations and conditions refer to Example 1.

[0036] After testing, the titanium dioxide content of the obtained titanium-rich material product was 80.32%, the calcium magnesium (CaO+MgO) impurity content was 7.87%, and the titanium recovery rate was 65.28%.

[0037] It can be seen from this comparative example that the static electrode voltage of the electrostatic separation is too large, resulting in more titanium-containing components entering the intermediate conductor, reducing the titanium recovery rate, and also reducing the titanium grade of the electrostatic pre-enriched material and the final product.

[0038] Comparative Example 3

[0039] Compared with Example 1, the only difference is that the electrostatic pre-enriched material is oxidatively roasted in an air atmosphere at a roasting temperature of 650° C. for 3 hours. Other operations and conditions are the same as those in Example 1.

[0040] After testing, the titanium dioxide content of the obtained titanium-rich material product was 86.67%, the calcium and magnesium (CaO+MgO) impurity content was 4.67%, and the titanium recovery rate was 52.18%.

[0041] It can be seen from this comparative example that: the roasting temperature is too low, the low-valent titanium is not fully oxidized, the titanium loss during the acid leaching process is large, and the titanium grade and titanium recovery rate of the product are both reduced.

[0042] Comparative Example 4

[0043] Compared with Example 1, the only difference is that the ball-milled material is leached with 30% sulfuric acid at 70°C for 2 hours, and the leaching liquid-to-solid ratio is 5 mL / g. Other operations and conditions are the same as those in Example 1.

[0044] After testing, the titanium dioxide content of the obtained titanium-rich material product was 75.54%, the calcium magnesium (CaO+MgO) impurity content was 13.38%, and the titanium recovery rate was 71.93%.

[0045] This comparative example shows that when sulfuric acid is used for acid leaching, calcium, magnesium and other phases remain in the leaching residue as solid phases, the titanium grade of the product decreases, and the impurity content increases significantly.

Claims

1. A method for extracting titanium and removing impurities from low-quality titanium-containing waste, characterized in that: The low-quality titanium-containing waste is sequentially subjected to magnetic separation for iron removal, grinding I and step-by-step electrostatic separation to obtain a pre-enriched material; the pre-enriched material is placed at a temperature of 800-1000°C for oxidative roasting to obtain a roasted slag containing rutile titanium dioxide; the roasted slag is subjected to grinding II and pickling to remove impurities to obtain a high-grade titanium-rich material product; The low-quality titanium-containing waste material includes at least one of the scraps or cuttings produced during the production process of the titanium alloy; In the process of the cascade electrostatic separation, the concentrate of the previous electrostatic separation is used as the raw material of the next electrostatic separation, and the processes are carried out in sequence; The step electrostatic separation includes 1 to 3 electrostatic separation processes, and the electrostatic separation condition parameters are: the roller speed is 80 to 140 rpm, and the static electrode voltage is 18 to 24 kV. When the step electrostatic separation includes 1 to 3 electrostatic separation processes, the roller speed decreases gradually as the number of electrostatic separations increases; The number of electro-selections included in the cascade electro-selection is determined according to the titanium grade in the titanium-containing waste. When the titanium grade is greater than 35%, only one electro-selection is carried out; when the titanium grade is 25%-35%, two electro-selections are carried out; when the titanium grade is less than 25%, three electro-selections are carried out; the pickling and impurity removal uses hydrochloric acid solution and / or nitric acid solution with a mass concentration of 10%-30% as the washing liquid.

2. The method for extracting titanium and removing impurities from low-quality titanium-containing waste according to claim 1, characterized in that: The grinding I controls the particle size of the material to be between 40 mesh and 180 mesh.

3. The method for extracting titanium and removing impurities from low-quality titanium-containing waste according to claim 1, characterized in that: The oxidative roasting is carried out in an oxygen-containing atmosphere; The oxidative roasting time is 2 to 4 hours.

4. The method for extracting titanium and removing impurities from low-quality titanium-containing waste according to claim 1, characterized in that: The grinding II controls the particle size of the material to be less than 180 mesh.

5. According to the method for extracting titanium and removing impurities from low-quality titanium-containing waste as described in claim 1, the conditions for pickling and removing impurities are: liquid-to-solid ratio is 3~8mL:1g, temperature is 50~90℃, and time is 1~3h.

6. A method for extracting titanium and removing impurities from low-quality titanium-containing waste according to claim 1, 2, 3 or 4, characterized in that: The high-grade titanium-rich material product has a titanium dioxide mass content of 92% to 95%, and a magnesium and calcium mass content of less than 1.5%.

Citation Information

Patent Citations

  • Method for preparing artificial rutile from high titanium slag

    CN107399758A

  • Method for preparing high-grade artificial rutile by low-grade titanium ore

    CN107285375A

  • Process method for recovering ilmenite from beach placer

    CN114505172A